2001
DOI: 10.1002/jmri.1170
|View full text |Cite
|
Sign up to set email alerts
|

Volume‐localized two‐dimensional correlated magnetic resonance spectroscopy of human breast cancer

Abstract: A localized 2D correlation spectroscopic sequence (L-COSY) was implemented and applied in human breast cancer in vivo to evaluate the water to fat (both saturated and unsaturated) ratios and also to identify choline. Being in agreement with the conventional 1D magnetic resonance spectroscopy (MRS) results, elevated water to lipids ratios were found in breast cancers and choline was observed only in a few cancer patients. J. Index terms: 1 H MR spectroscopy; saturated fatty acid; unsaturated fatty acids; water;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 16 publications
7
45
0
Order By: Relevance
“…It has been reported that mice tumors contain 84% water by tissue weight, whereas fat accounts for only 12% (37). It was recently reported that the reduction in fat signal is most probably due to the loss of mammary fat tissue in breast cancer (38). This may be one reason for the reduced lipid signal observed in most breast cancer patients in our study.…”
Section: Discussionsupporting
confidence: 47%
“…It has been reported that mice tumors contain 84% water by tissue weight, whereas fat accounts for only 12% (37). It was recently reported that the reduction in fat signal is most probably due to the loss of mammary fat tissue in breast cancer (38). This may be one reason for the reduced lipid signal observed in most breast cancer patients in our study.…”
Section: Discussionsupporting
confidence: 47%
“…The presence of ZQC during TM leads to 2D ZQ-filtered COSY cross peaks (12,18). The ZQ-filtered COSY cross peaks of an oil phantom look similar to a COSY spectrum of a healthy human breast in vivo showing the J-connectivities between the protons of unsaturated and saturated lipids (26). Two pairs of cross peaks were identified at the following locations: C1 (F 2 ϭ 5.4 ppm, F 1 ϭ 2.9 ppm), C2 (F 2 ϭ 5.4 ppm, F 1 ϭ 2.2 ppm), C1Ј (F 2 ϭ 2.9 ppm, F 1 ϭ 5.4 ppm), and C2Ј (F 2 ϭ 2.2 ppm, F 1 ϭ 5.4 ppm).…”
Section: Shown Inmentioning
confidence: 78%
“…For in vivo measurements, MR spectroscopic data is complicated by the inherent overlap and complex shapes of the signals of interest. Methods to improve detection of specific spectral contributions include spectral editing [4,18,28,33,[46][47][48]; spectral fitting using constrained parametric model optimization and incorporating a priori metabolic information [6,7,23,24,31,35,40,45,50]; and use of multidimensional spectral acquisition methods [42][43][44]. In all of these areas of research, spectral simulation methods are becoming an increasingly important tool.…”
Section: Introductionmentioning
confidence: 99%